Penerapan Metode Prototyping Pada Aplikasi Sentra Pelayanan Kepolisian Terpadu Berbasis Web - Mardhiah Fadhli; Annisa Marion (Indonesian Society of Applied Science, 2022)
The community considers that the services managed by the police seem less effective and efficient. Due to public complaints at this time, the community really needs information and fast service at the SPKT (Integrated Police Service Center). Services provided by SPKT, especially services for lost goods, for those who have lost their Vehicle Number Certificate (STNK), Car/Motorcycle, Driving License (SIM) for Car/Motorcycle, Identity Card (KTP), Family Card (KK), Automated Teller Machine (ATM) , Savings Books, Passports, Student Identity Cards (KTM), and others. At the Pekanbaru Police, when a complaint or complaint from the SPKT (Integrated Police Service Center) police unit is still manual where the making of the letter of loss is still using Microsoft Word by deleting and replacing the contents of the file. The purpose of this research is to assist the public in providing clear information and getting lost more easily and to facilitate the management of lost data from the community in order to determine the points where the loss of goods occurred. This system was built using the Protoyping Method, which is a method to get an overview of the system obtained from the user first, then it will be visited by the user so that it can be a reference for system development. The result of the user acceptance test (UAT) from the implementation of the program is that 100% functionality in the application is acceptable